Avoiding artefacts during electron microscopy of silver nanomaterials exposed to biological environments - Chen,S; Goode,AE; Skepper,JN; Thorley,AJ; Seiffert,JM; Chung,KF; Tetley,TD; Shaffer,MSP; Ryan,MP; Porter,AE (Journal of Microscopy, 2015)
Electron microscopy has been applied widely to study the interaction of nanomaterials with proteins, cells and tissues at nanometre scale. Biological material is most commonly embedded in thermoset resins to make it compatible with the high vacuum in the electron microscope. Room temperature sample preparation protocols developed over decades provide contrast by staining cell organelles, and aim to preserve the native cell structure. However, the effect of these complex protocols on the nanomaterials in the system is seldom considered. Any artefacts generated during sample preparation may ultimately interfere with the accurate prediction of the stability and reactivity of the nanomaterials. As a case study, we review steps in the room temperature preparation of cells exposed to silver nanomaterials (AgNMs) for transmission electron microscopy imaging and analysis. In particular, embedding and staining protocols, which can alter the physicochemical properties of AgNMs and introduce artefacts thereby leading to a misinterpretation of silver bioreactivity, are scrutinized. Recommendations are given for the application of cryogenic sample preparation protocols, which simultaneously fix both particles and diffusible ions. By being aware of the advantages and limitations of different sample preparation methods, compromises or selection of different correlative techniques can be made to draw more accurate conclusions about the data. Lay description: With increasing commercialization of silver nanomaterials (AgNMs) comes a concomitant need to understand occupational health, public safety and environmental implications of these materials. Nanoscale studies of the complex bio-nano interface lie at the heart of technical challenges. Despite numerous reports, there is no consensus regarding biological mechanisms enacted by AgNMs. Powerful new electron microscopy techniques can be used to visualize the interaction of the AgNMs with tissues. However, it is extremely difficult to